HIDROLISAT KOLAGEN DARI LIMBAH PADAT KULIT SAMAK SEBAGAI COATING SUPERABSORBENT PADA PUPUK LAMBATURAI: SEBUAH LITERATUR REVIEW - Febriani Purba, Ono Suparno, Ani Suryani, Is Fatimah (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
The leather tanning industryis identical with eco-unfriendly due to the high production of waste. There are two type of solid waste, namely chromium-containing solid waste and chromium-free solid waste. This review discussed the latest studies that have been done in the utilization of chromium-containing solid waste, superabsorbent, and slow release fertilizer. Hydrolized collagen (h-collagen) is a major ingredient in this solid waste. H-collagen has the potential to be used as the second coating on the engineering of slow-release fertilizer so it has the power as superabsorbent (SAP). H-collagen has many reactive hydrophilic groups which can be modified to increase its hydrophilicity thus replacing synthetic polymers in theSAP manufacturing. The separation of chromium from the solid waste is the first thing to do before the utilization of the collagen contained therein. H-collagen utilization from the solid waste of leather is expected to produce a natural SAP at a cheaper price and environmentally friendly. Keywords: leather-tanning solid waste, collagen hydrolysates, superabsorbent, slow release fertilizer